2011
DOI: 10.1029/2011gl049921
|View full text |Cite
|
Sign up to set email alerts
|

Fast slip-rate along the northern end of the Karakorum fault system, western Tibet

Abstract: The exact location of the northern Karakorum fault (KF) in western Tibet is unclear and its current activity is debated. Here, we investigate the possible northern extension of the KF, the Muji fault, located in the Chinese Pamir, which belongs to the Kongur Shan extensional system, and provide the first quantitative estimate of its Holocene slip‐rate. The fault cuts and offsets a series of 6 fluvial terraces, yielding a minimum slip‐rate of 4.5 ± 0.2 mm/yr, by matching the largest terrace riser offset with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
(76 reference statements)
8
51
0
1
Order By: Relevance
“…Additionally, the Dabudar glacial stage deposits that show no lateral separation where they overlie the Achiehkopai fault strand indicate that neither strand of the northern Karakoram fault has carried detectable slip for ∼200 ka or longer. While this interpretation is not as robust as for the Hangdi glacial stage deposits given the highly eroded nature of the Dabudar glacial deposits, Dabudar glacial stage landforms would be expected to show 1-2 km of lateral offset for slip rates of 5-10 mm/yr (Chevalier et al, 2011(Chevalier et al, , 2005, which they clearly do not. Further, the truncation of the topographic scarps in the Dabudar glacial stage deposits by the Tashkorgan glacial stage deposits show they are older than 65 ka, regardless of their origin.…”
Section: Late Quaternary Slip History Of the Northern Karakoram Faultmentioning
confidence: 93%
See 3 more Smart Citations
“…Additionally, the Dabudar glacial stage deposits that show no lateral separation where they overlie the Achiehkopai fault strand indicate that neither strand of the northern Karakoram fault has carried detectable slip for ∼200 ka or longer. While this interpretation is not as robust as for the Hangdi glacial stage deposits given the highly eroded nature of the Dabudar glacial deposits, Dabudar glacial stage landforms would be expected to show 1-2 km of lateral offset for slip rates of 5-10 mm/yr (Chevalier et al, 2011(Chevalier et al, , 2005, which they clearly do not. Further, the truncation of the topographic scarps in the Dabudar glacial stage deposits by the Tashkorgan glacial stage deposits show they are older than 65 ka, regardless of their origin.…”
Section: Late Quaternary Slip History Of the Northern Karakoram Faultmentioning
confidence: 93%
“…Several studies of offset geomorphic features have proposed relatively rapid Quaternary slip rates on the Karakoram fault of 7-12 mm/yr along the entire trace of the fault from southeast Tibet to the Pamir (Fig. 1B) (Chevalier et al, 2011(Chevalier et al, , 2005(Chevalier et al, , 2012. Other studies yield considerably slower Quaternary slip rates along the southern portion of the fault system (∼4 mm/yr; Brown et al, 2002Brown et al, , 2005, or have suggested that the northern portion of the Karakoram fault has been inactive during the Quaternary (Robinson, 2009a) with active extension along the Kongur Shan extensional system unrelated to slip on the Karakoram fault (Robinson et al, 2004(Robinson et al, , 2007.…”
Section: Regional Geologymentioning
confidence: 98%
See 2 more Smart Citations
“…Satellite remotely sensed images and stream terrace studies show that the Muji fault is a dextral strike-slip structure [7,20]. Based on the cosmogenic nuclide dating method, Chevalier et al [21] revealed that the right-lateral slip rate along the Muji fault is 4.5-11 mm/year, and the lithology of the footwall is characterized by mixed Paleozoic metamorphic [7]. As seen from Figure 1, in the Tien Shan and Pamir regions, the GPS-inferred crustal movement velocity exhibits a substantial decreasing trend from the south to north, a well-documented rapid crustal shortening phenomenon, characterized by features of the widespread active faulting and folding, as well as the recent crustal arching and high regional seismicity [22].…”
Section: Tectonic Settingmentioning
confidence: 99%